PENGARUH GAYA KEPEMIMPINAN DAN PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN PT. DJAS SUCCES SUPPORT - Vera Alriani; Sastra Tamami; Dhenny Asmarazisa (EQUILIBIRIA, 2017)
This research was conducted at PT. Succes Djas Support. The purpose of this study was to determine the influence of Leadership Style and Incentives to Employee Performance. In this study, the authors used a sample of 35 people who were taken out of the total population (employees). While the types of data used are primary data and secondary data. Sources of primary data obtained from questionnaires obtained from employees of PT. Succes Djas Support. While the secondary data obtained from the document PT. Support and Success Djas of related literature and can support as well as useful for this research. Data was collected through interviews and questionnaires. Data analysis using descriptive statistical method that describes and gives an overview of the object under study through the data with methods drawn from a population sample obtained in the field associated with the relevant theories and techniques of quantitative analysis of the data that has been given a score according to the scale of measurement used the Likert scale and the results of the test using SPSS 17. From the research, the authors conclude that partial Leadership Style (X1) has a positive and significant effect on Employee Performance (Y), with the t test results counted at 2,226 while Incentives (X2) has a positive and significant effect on Employee Performance (Y) , it is seen from the test results of 3,330 t counted. But simultaneously Leadership Style and Incentives has a positive and significant effect (strong) on Employee Performance in PT. Succes Djas Support, with the value of F counted 18 703.